2008
DOI: 10.1002/jae.1005
|View full text |Cite
|
Sign up to set email alerts
|

An alternative approach to estimate the wage returns to private‐sector training

Abstract: This paper follows an alternative approach to identify the wage effects of privatesector training. The idea is to narrow down the comparison group by only taking into consideration the workers who wanted to participate in training but did not do so because of some random event. Narrowing down the participant and comparison group makes them increasingly similar on observed characteristics, supporting the validity of the approach. At the same time the point estimate of the return to training consistently drops f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 22 publications
5
115
1
8
Order By: Relevance
“…An extensive literature estimates the wage returns of training investments. The general finding is that private returns are high, although studies that account for potential endogeneity, found much lower returns (Leuven and Oosterbeek, 2004;Leuven and Oosterbeek, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…An extensive literature estimates the wage returns of training investments. The general finding is that private returns are high, although studies that account for potential endogeneity, found much lower returns (Leuven and Oosterbeek, 2004;Leuven and Oosterbeek, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Another approach to estimate training returns that neither relies on panel data nor on exclusion restrictions was suggested by Leuven and Oosterbeek (2008), henceforth LO. This approach defines a group of non-participants that is assumed to have similar characteristics as the group of participants.…”
Section: Introductionmentioning
confidence: 99%
“…While the monetary returns refer to an increase in worker's productivity which is expected to elevate his future earnings (Lynch, 1992;Mincer, 1989a;Pischke, 2001;Evertsson, 2004), non-monetary returns refer to returns such as promotion, employment stability (Büchel & Pannenberg, 2004) and job security (Bassanini, 2006;Lang, 2012), all of which are expected to rise with the training investment. Although there are only few empirical studies concentrating on the relation between training and nonmonetary returns, recent studies have pointed to a weak correlation between training and wages which is in contrast to the human capital theory (Pischke, 2001;Leuven & Oosterbeek, 2008;Görlitz, 2011).…”
Section: The Human Capital Theory: the Concept Of Trainingmentioning
confidence: 92%